2005
DOI: 10.4049/jimmunol.174.4.1922
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of NKG2D by Cognate Ligand or Antibody Alone Is Insufficient to Mediate Costimulation of Human and Mouse CD8+ T Cells

Abstract: CD8+ T cells require a signal through a costimulatory receptor in addition to TCR engagement to become activated. The role of CD28 in costimulating T cell activation is well established. NKG2D, a receptor found on NK cells, CD8+ αβ-TCR+ T cells, and γδ-TCR+ T cells, has also been implicated in T cell costimulation. In this study we have evaluated the role of NKG2D in costimulating mouse and human naive and effector CD8+ T cells. Unexpectedly, in contrast to CD28, NKG2D engagement by ligand or mAb is not suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 29 publications
5
73
1
Order By: Relevance
“…Similar discrepancies have been observed for resting and IL-2-activated NK cells, where several of the major activating receptors fail to stimulate resting NK cells when triggered alone [24]. Moreover, our results are in agreement with data demonstrating that NKG2D engagement by ligand or stimulatory antibodies is not sufficient to co-stimulate naive or effector CD8 1 T-cell responses in conventional T-cell populations [32].…”
Section: Discussionsupporting
confidence: 91%
“…Similar discrepancies have been observed for resting and IL-2-activated NK cells, where several of the major activating receptors fail to stimulate resting NK cells when triggered alone [24]. Moreover, our results are in agreement with data demonstrating that NKG2D engagement by ligand or stimulatory antibodies is not sufficient to co-stimulate naive or effector CD8 1 T-cell responses in conventional T-cell populations [32].…”
Section: Discussionsupporting
confidence: 91%
“…The engagement of NKG2D resulted in enhanced CTL expansion, IFN-␥ secretion, and CTL activity, suggesting that NKG2D is a costimulatory molecule sharing functional similarities with CD28 (60). These findings differ from those of Ehrlich et al (25), in which a rigorous analysis indicated that NKG2D expression on mouse CD8 ϩ T cells acts as a costimulatory molecule only under restricted conditions or requires additional cofactors. The experimental conditions and model systems employed may explain the differences between these results.…”
Section: Discussioncontrasting
confidence: 56%
“…During priming, naïve CD8 ϩ T cells require T-cell receptor (TCR) engagement to MHC molecules presenting antigenic peptide and secondary costimulatory signals, such as CD28 ligation by members of the B7 family, in order to expand and differentiate into CTLs (88). Importantly, the costimulation of antigen-primed CTLs is not required for the release of effector molecules, but it can enhance effector functions (25,51,60). T cells express numerous receptors that act in controlling cellular responses through recognition and binding to specific ligands (88).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the concomitant down-regulation of H60 and up-regulation of MHC class I proteins on tumor cells would effectively convert them from NK cell targets to CD8 ϩ T cell targets. Although some studies have shown a positive role for murine NKG2D receptor-ligand interactions in costimulating CD8 ϩ T cell proliferation and cytotoxicity (17,48), other studies have found no role for this ligand-receptor system in affecting T cell function (49) and some even report that certain NKG2D ligands can inhibit CD8 ϩ T cell function in an NKG2D-independent manner (50). Indeed, our preliminary finding is that IFN-␥ treatment of the F244 sarcoma line enhanced its recognition by a T cell line while inhibiting its recognition by NK cells (J. D. Bui and R. D. Schreiber, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%